Challenges and mitigation strategies during contact tracing: Lessons learned in COVID-19-pandemic - Suraj Kapoor; Vivek Anand; Arun Kumar Yadav; S Vijay Bhaskar; Surinder Kumar; Dharamjeet Singh Faujdar; Prabhakar Teli (Wolters Kluwer Medknow Publications, 2022)
Introduction: Contact tracing can identify potentially infected individuals before severe symptoms emerge, and if conducted sufficiently quickly can prevent onward transmission from secondary cases. This study has been conducted to find challenges and mitigation strategies in contact tracing during the COVID-19 pandemic. Methodology: A cross-sectional descriptive study was conducted among health care professionals involved in contact tracing using an online questionnaire. The participants were asked about challenges faced during contact tracing and the usefulness of mitigation strategies. Results: A total of 302 health care professionals with a mean age of 34.69 ± 5 years participated in the study. Various strategies employed by agencies during contact tracing included measures to reduce stigma, community participation, and the use of digital tools and technology. Among the most common challenges faced by the study participants, 68% felt contacts being unreachable a major challenge, while 54.3% found difficulty in contact identification. Approximately 39% of doctors, 26% of nurses, and 17% of paramedical staff faced language/communication problems. Conclusion: Training health care professionals on the key aspects of contact tracing, the use of the latest technology, mitigation of stigma by health education may help in overcoming challenges during contact tracing in the COVID-19 pandemic.